Meus alunos devem saber ler e contar : (re)significando o ensino de Ciências e Geografia nas séries iniciais - Brito, Fernanda Rosa de (2007)
This study focuses on the analysis of study situations from a proposal with globalized approach involving the education of Sciences and Geography of the third grade of Elementary school, searching in the teaching practices for the evidences, indications of the educational processes and learning involvements. The challenge of this inquiry accomplishment has the desire to contribute more for the reconstruction of a proposal of education more adequate with the current context, with improvement views of the education of Sciences and Geography. The inquiry is the qualitative type, having as main source of data the observation, field notes, interviews and questionnaire. Students of the third grade of Elementary school had participated in the research, the regent teacher and the School s coordinator. The results reveal that the construction of a structured pedagogical practice in a globalized perspective of knowledge is possible, in which the students under the teacher s intercession can have a broader and deeper view of the education of Sciences and Geography.